Cryopreservation and oxidative stress in porcine oocytes. (March 2021) - Mateo-Otero, Yentel; Yeste, Marc; Damato, Anna; Giaretta, Elisa
Abstract: Several vitrification protocols have been established for porcine oocytes so as to facilitate gene banking of female germplasm. Although live piglets have been successfully produced from pig oocytes vitrified at the germinal vesicle (GV) stage, the competence of vitrified oocytes to develop into the blastocyst stage is greatly compromised following cryopreservation. The focus of this review is to elucidate the impact of cryopreservation on the redox balance of pig oocytes, making special reference to the relevance of non-enzymatic and enzymatic antioxidant defences. Besides, the regulation of gene expression in response to oxidative stress is also considered. Finally, we discuss the effects of supplementing maturation and vitrification media with the exogenous non-enzymatic antioxidants that have hitherto yielded the most relevant results. Highlights: Pig oocyte are cryopreserved through vitrification. Vitrification alters the redox balance of pig oocytes. Adding non-enzymatic antioxidants to vitrification media improves oocyte cryotolerance.